Implementation of TOPSIS in a Decision Support System for Selecting the Ideal Food Menu for GERD Patients - Jesica Emarapenta Br Sinulingga; Annisaa Utami (Research Group of Data Engineering, Faculty of Informatics, 2025)
Gastroesophageal Reflux Disease (GERD) is a condition characterized by the repeated reflux of stomach acid into the esophagus, causing symptoms such as heartburn and regurgitation. This condition can be triggered by irregular eating habits, including improper portion sizes, frequency, or types of food. Frequent consumption of foods that are excessively hot, spicy, or acidic can exacerbate stomach problems by increasing gastric acid production, leading to GERD recurrence. This study aims to develop a web-based decision support system to determine the ideal food menu for GERD patients. The system utilizes five main criteria protein, carbohydrates, fat, fiber, and calories to analyze ten food menu alternatives. The comparison between the system's results and manual calculations demonstrates consistent outcomes, as both produce identical preference index values. Based on the calculations, Wheat Pasta was determined as the most ideal food menu with the highest preference index value of 0.7415. Other menus, such as Kalasan Fried Chicken, Salmon Fish, and Stir-fried Tempe, also had high preference indexes, while menus such as Stir-fried Chayote, Stir-fried Spinach, and Oatmeal ranked lower.